Analisis Kontrol Diri Siswa Saat Belajar dari Rumah dalam Menggunakan Handphone pada Masa Pandemi COVID-19 - Zulpi Hendra; Hengki Yandri; Harmalis Harmalis (Indonesian Journal of Counseling and Development, 2021)
This research is motivated by indications that students have not been able to control themselves in the use of mobile phones, so it can negatively affect students. This study aims to analyze students' self-control when learning from home in using mobile phones during the Covid-19 outbreak. This study is a type of descriptive quantitative research with a research population of all students of State Junior High School 3 Sungai Penuh numbering 149 people, then the sample of this study was taken with total sampling techniques. The study data was collected using a scale of students' self-control in mobile phone use, then analyzed data using descriptive statistics. The results showed that the level of self-control of students in using mobile phones during the Covid-19 pandemic in aspects of self-control, diligent despite many obstacles, behaving according to rules and norms, controlling emotions, and the ability to adjust to be in the moderate category. For that, to the next researcher, it is expected to conduct research by conducting treatment to research subjects so that the ability of students in controlling themselves becomes better, especially in the use of mobile phones